Further development of a laboratory procedure to assess the mechanical performance of cob. Issue 3 (4th May 2018) - Vinceslas, Théo; Hamard, Erwan; Razakamanantsoa, Andry; Bendahmane, Fateh
Abstract : Cob is a vernacular earth-building technique which has encountered renewed interest for its low environmental impact compared to conventional construction materials. Relevant mechanical characterisation is essential for cob building structure design and calculation. This paper presents an improved laboratory procedure to better the characterisation of representative cob samples. Samples prepared by four different methods were compared to representative cob wall elements, by measuring shrinkage ratio, pore size distribution, uniaxial compressive strength and Young's modulus. The preliminary laboratory testing provides satisfactory results but needs to be validated with other cob mixtures.